Réponses

2014-01-02T19:53:34+01:00
Bonsoir

1) A = (3y - 2)² - (3y - 2)(5y + 7)
A = (9y² - 12y + 4) - (15y² + 21y - 10y - 14)
A = 9y² - 12y + 4 - 15y² - 21y + 10y + 14
A = -6y² -23y + 18

2) A = (3y - 2)² - (3y - 2)(5y + 7)
A = (3y - 2)(3y - 2) - (3y - 2)(5y + 7)
A = (3y - 2)[(3y - 2) - (5y + 7)]
A = (3y - 2)(3y - 2 - 5y - 7)
A = (3y - 2)(-2y - 9)
2014-01-02T19:56:43+01:00
Bonsoir
A = (3y - 2)² - (3y - 2)(5y + 7) 1) Développer et réduire A.   2) Factoriser A.

A = 9y² - 12y +4 - (15y² +21y -10y -14)
A = 9y² -12y +4 -15y² -21y +10y +14
A = - 6y² -23y +18

A = (3y-2)(3y-2)- (5y+7)
A = (3y-2)(3y-2  +5y -7)
A = (3y-2)( 8y -9)